A multisource feedback tool to assess ward round leadership skills of senior paediatric trainees: (2) Testing reliability and practicability. Issue 1075 (4th May 2015) - Goodyear, Helen M; Lakshminarayana, Indumathy; Wall, David; Bindal, Taruna
ABSTRACT: Background: A five-domain multisource feedback (MSF) tool was previously developed in 2009–2010 by the authors to assess senior paediatric trainees' ward round leadership skills. Objectives: To determine whether this MSF tool is practicable and reliable, whether individuals' feedback varies over time and trainees' views of the tool. Methods: The MSF tool was piloted (April–July 2011) and field tested (September 2011–February 2013) with senior paediatric trainees. A focus group held at the end of field testing obtained trainees' views of the tool. Results: In field testing, 96/115 (84%) trainees returned 633 individual assessments from three different ward rounds over 18 months. The MSF tool had high reliability (Cronbach's α 0.84, G coefficient 0.8 for three raters). In all five domains, data were shifted to the right with scores of 3 (good) and 4 (excellent). Consultants gave significantly lower scores (p<0.001), as did trainees for self–assessment (p<0.001). There was no significant change in MSF scores over 18 months but comments showed that trainees' performance improved. Trainees valued these comments and the MSF tool but had concerns about time taken for feedback and confusion about tool use and the paediatric assessment strategy. Conclusions: A five-domain MSF tool was found to be reliable on pilot and field testing, practicable to use and liked by trainees. Comments on performance were more helpful than scores in giving trainees feedback.